ROLE AND SIGNIFICANCE OF ULTRASOUND IN SPORT MEDICINE - A.O. Matkarimov (Galaxy International Interdisciplinary Research Journal, 2021)
Ultrasonography (US) is a safe and noninvasive imaging modality that is gaining popularity in different medical and surgical fields. Its introduction in musculoskeletal and sports medicine has taken this advanced subspecialty to a higher level. It has the advantage over other imaging techniques with regards to ease of use, availability, comfort and cost. Not to mention, in terms of safety profile, patients are not exposed to radiations, like in x-rays, and it can be performed on patients with metal or pacemaker implants, which are contraindicated in MRI. Standard diagnostic sonography doesn’t have any known harmful effects on humans. In this article we will discuss the role of ultrasound in sports medicine, highlighting the diagnostic and interventional indications, uses and limitations.